Linking mental health disorders to childlessness: The roles of disorder type and partnership - Kailaheimo-Björkqvist, Sanna; Nisén, Jessica; Metsä-Simola, Niina; Martikainen, Pekka; Myrskylä, Mikko (University of Bamberg Press, 2026)
Objective: Drawing on a life-course perspective that emphasises partnership-related processes, we examine how different mental health disorders relate to childlessness and whether these associations are explained by partnership status and partner’s mental health.
Background: Mental health problems are increasing, while childlessness is becoming more common.
Method: We use Finnish total population register data and discrete-time event history models to estimate the annual likelihood of having a first child.
Results: All types of mental health disorders are associated with a lower likelihood of first-time childbearing. In age-controlled models, the annual probability 0.8-1.3%-points lower for women and 1.0-1.8%-points for men, with the strongest associations observed for severe mental disorders. Accounting for partner’s mental health and partnerships attenuates these associations, particularly among men (for any mental health disorder, 13% for women and 36% for men compared with age-controlled models).
Conclusion: Partnerships and partner's mental health are important in understanding the association between mental health disorders and childlessness across the life course, especially among men.